Analysis of Three Different Silencer Nozzles in Reducing Airgun Noise for Occupational Safety and Health by Using IMMI Software - Tau, Wei Ming; Azmir, Nor Azali (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Noise exposure is a serious problem in industrial environments which poses significant risks to workers’ health and safety. This study aimed to address this issue by evaluating the use of normal airguns and the effectiveness of silencer nozzles in reducing noise levels. Objectives included mapping noise exposure in a production area, simulating and selecting the best silencer nozzle based on noise reduction performance and comparing the simulated noise exposure levels with Malaysian occupational safety and health standards. Using IMMI simulation software, noise maps showed that normal airguns contributed to hazardous noise exposure. To mitigate this, three silencer nozzles: CEJN, Silvent and Chicago Pneumatic were tested as replacements. The Chicago Pneumatic model proved most effective in reducing noise by up to 41 dB(A). Further analysis using the ICOP equation calculated daily noise exposure levels for workers showed that silencer nozzles significantly reduced noise exposure to below permissible limits. Results showed that while normal airguns exceeded safe noise levels, silencer nozzles maintained levels well within safety thresholds which enhances workplace safety. The study concluded that silencer nozzles were effective in lowering noise exposure levels in industrial settings and enhancing workplace safety which highlights the importance of implementing noise control measures and utilizing simulation software for accurate noise reduction predictions.